Do young children, like young adults, remember animates better than inanimates? - Bugaiska, Aurélia; Bonin, Patrick; Witt, Arnaud (Frontiers in Psychology, 2023)
It has repeatedly been shown in adults that animates are remembered better than inanimates. According to the adaptive view of human memory (Nairne, 2010, 2015), this is due to the fact that animates are generally more important for survival than inanimates. Animacy enhances not only the quantity but also the quality of remembering. The effect is primarily driven by recollection (Bonin et al., 2014; Bugaiska et al., 2016). Virtually all studies have been conducted in adults, and we believe that the investigation of animacy effects in children is also highly relevant. The present study therefore tested the animacy effect on recollection in young (6–7 years, M = 6.6 years) and older children (10–12 years, M = 10.83 years) using the Remember/Know paradigm (Gardiner, 1988). As found in adults, an animacy effect on memory was found, but only in older children, and specifically in the “remember” responses, suggesting, once again, its episodic nature.